KAJIAN PENDUGAAN EROSI SUB DAERAH ALIRAN SUNGAI TUGU UTARA (CILIWUNG HULU) - Nono Sutrisno Sa'ad (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2004)
The research of erosion prediction method at the watershed scale was carried out at Tugu Utara (Upper Ciliwung) sub-watershed in Puncak, West Java, Indonesia from August 2000 to February 2001. The objectives of this study were: ( I ) to predict erosion at watershed scale through an approximation of sediment yield measurement at the outlet of subwatershed, and (2) multiple regression equation and Sediment Delivery Ratio (SDR) prediction. The experiment at Tugu Utara (upper Ciliwung) sub-watershed measured the discharge, surface erosion by soil pan method, sediment yield by sampling at the outlet and SDR. The result showed that the multiple regression equation and SDR Stiff Diagram can be used to predict the erosion at Tugu Utara (upper Ciliwung) sub-watershed. Keywords: Erosion prediction, multiple regression equation, sediment delivery ratio.